2003
DOI: 10.1186/bcr651
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin expression in primary carcinomas of the breast and its distant metastases

Abstract: IntroductionTumor invasion with subsequent metastases is the major cause of morbidity and mortality in patients with cancer. For patients with breast cancer, the development of metastases is the most important prognostic factor, as almost all patients with distant metastasis succumb to the disease [1][2][3].Numerous studies have linked aberrant expression of E-cadherin with the development of metastases in breast cancer and other cancers. E-cadherin is a transmembrane glycoprotein that mediates calcium-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
288
2
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(325 citation statements)
references
References 22 publications
25
288
2
10
Order By: Relevance
“…However, somatic mutations in E-CD gene have been found in only 56% ILCs (14). Cytoplasmic positivity, as noticed in two cases of ILC in present study, has also been reported by other workers 30,31 This different pattern of E-CD expression in invasive ductal and lobular carcinomas suggests that this protein molecule plays different role in the two morphologic types. In cases of ductal carcinomas with lobular differentiation, we observed a mixed pattern of staining.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, somatic mutations in E-CD gene have been found in only 56% ILCs (14). Cytoplasmic positivity, as noticed in two cases of ILC in present study, has also been reported by other workers 30,31 This different pattern of E-CD expression in invasive ductal and lobular carcinomas suggests that this protein molecule plays different role in the two morphologic types. In cases of ductal carcinomas with lobular differentiation, we observed a mixed pattern of staining.…”
Section: Discussionsupporting
confidence: 86%
“…Thirty-five percent cases showed positive E-CD staining in the deposits. Similar observations were reported in distant metastatic tumor deposits by Kowalski et al 30 There is growing evidence that carcinoma cells, which loose E-CD expression, may re-express it once 45 they reach distant sites. Underlying reasons for this re-expression might be related to the fact that tumor cells require to gain certain molecules that would enable them to adhere to different stromal components and endothelial cells at foreign sites, which they loose at the time of being uprooted from primary site, where the expression gets lost.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Further support for the putative role of our RAMBAs as differentiating agents came from the findings that VN/14-1 caused a dose-dependent up-modulation (from four-to six-fold) of ER-a protein, another differentiation marker. The ability of these RAMBAs to induce differentiation in breast cancer cells may be of significance in light of recent findings which suggest that downregulated expressions of CK 18 (Korsching et al, 2002;Woelfle et al, 2004;Schaller and Buhler, 2005) and/or E-cadherin/ ER-a (Nass et al, 2000;Kowalsski et al, 2003) promote progression of human breast cancer. It should be noted that differentiated tumour cells exhibit low proliferative and metastatic potential.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the expression of E-cadherin supports cohesive, collective cell migration/ invasion (Friedl and Gilmour, 2009). Although the loss of E-cadherin expression or function is a common event in tumor progression (Yap, 1998;Nollet et al, 1999), there is emerging evidence that the expression of E-cadherin during cancer progression may be dynamic and highly contextual (Kowalski et al, 2003). To date, E-cadherin regulates PTEN via b-catenin-Egr1 signaling M-T Lau et al the role of E-cadherin in ovarian cancer progression remains controversial, particularly in regards to its effects on cell growth.…”
Section: Regulation Of Pten Levels By Cell Density and E-cadherin-cadmentioning
confidence: 99%